PENGARUH LATIHAN INCREMENTAL VERTICAL HOP TERHADAP POWER OTOT TUNGKAI SISWA PERGURUAN SILAT WALET PUTI PEKANBARU - Maria Puspa Rija; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the observation results of the students martial arts Walet Puti Pekanbaru, by the time they kick, it will look like they have no kick up, no power and slow. To prove this, the test is conducted using a standing board jump test instrument intended to measure the leg muscle power. Test came back that students martial arts Walet Puti Pekanbaru still needed training to increase the leg muscle power. On this study, researchers focused on Incremental Vertical Hop exercise. This research was experimental research, the population was student martial arts Walet Puti SMK Negeri Pertanian Terpadu Pekanbaru, the data in this research is 10 samples of 12 populations. The instrument carried out in this research was a standing board jump, which aim to measure the leg muscle power. The data in this research was processed by using statistics, to test the normality by the lilliefors test at a significant level of 0.05. The hypothesis proposed that there was an effect of Incremental Vertical Hop exercise in leg muscle power. Based on the t-test analysis, Tvalue was 14,72 and Ttable was 1,833 which means Tvalue > Ttable. Based on statistical data analysis, the mean of Pre-Test was 209,5 and the mean of post-test was 231,3, which means the data were normal. Therefore, it can be concluded that there was an effect of the Incremental Vertical Hop exercise in leg muscle power students martial arts Walet Puti Pekanbaru.Key Words: Incremental Vertical Hop, Leg Muscle Power